Z problematyki kontroli związanej z płatnościami bezpośrednimi do gruntów rolnych w Polsce - Staniewska, Anna (Wydawnictwo Naukowe UAM, 2007)
An operational control system, or an adequate system of audit and monitoring is of significant importance for ensuring proper expenditure of the Community funds, and - for that matter - of a proper mechanism of effecting direct payments to land. The paper focuses on the question whether the system of checks and controls in the Polish legislative system is adequate to secure the appropriate level of monitoring of direct payments to land required in Community law. The paper is also an attempt to diagnose the difficulties encountered by Polish organs which are responsible for proper monitoring of the spending of Community funds. The paper ends with a conclusion that the management and the audit/ control systems are not integrated, and as a result there is no control over the management of direct payments to land in Poland.
ON THE MONITORING OF DIRECT PAYMENTS TO LAND IN POLAND